Student Government Associations: What Makes a Good Year? - Nadler, Daniel P.; Miller, Michael T. (Journal of Education and Training, 2025)
College student government associations have historically played an important role in both providing students an opportunity to learn about civic structures and responsibility along with providing a forum for the expression of student interests to the institution at large. Much like their public counterparts, however, it can be difficult to identify whether or not these bodies are performing effectively. The current study sought to identify, from student government advisors, leaders and members, how to evaluate their work over the course of a year. Although there were several significant differences identified between the three groups on data from a research-team developed survey, there was consensus around the ideas of passing legislation and doing work that matters to the student body at large and in meeting the needs of students as constituents.